Tren Penggunaan Tiktok dalam Komunikasi: Analisis Kuantitatif terhadap Perilaku Pengguna di Kalangan Mahasiswa Ilmu Komunikasi UINSU - Sandra Vanya; Dian Permatasari; Meika Ananda Priskarini; Aulya Fatahilla; Go Meylisa; Ahmad Fadil Hsb; Nursapia Harahap (IAI Nasional Laa Roiba Bogor, 2024)
This research analyzes the impact of TikTok use on teenagers' mental well-being, explores effective marketing strategies, and identifies factors that contribute to viral content. The focus is on TikTok user behavior among UINSU Communication Studies students, emphasizing content preferences, optimal posting times, and general engagement. Quantitative survey methods were used to collect data from a representative sample of students. Findings show TikTok as an important phenomenon with great influence from influencers, although its impact on communication skills varies. Additionally, TikTok shows potential as a learning tool but requires integration with traditional learning methods to ensure content quality and ethical awareness in its use. This research provides important insights for developing communication strategies and educational approaches at UINSU.